CURRENT STATUS ON CACAO DISEASE INCIDENCE IN CENTRAL SULAWESI - Nur Edy; Margaret Angelia; Irwan Lakani; Johanis Panggeso (AGROLAND The Agricultural Sciences Journal (e-Journal), 2019)
Central Sulawesi is the largest cocoa bean producer in Indonesia. However, cocoa production constrained by important diseases. Currently, data about cocoa beandamage due to pathogen infection have not been updated. This study observed the incidence of major diseases in cacao plantations, included pod rot, canker, and vascular-streak dieback (VSD). The study located at the largest cacao plantation in Palolo, Central Sulawesi. The observation pronounced that the cacao trees in the study sites were infected by the pathogens of pod rot, canker, and VSD with different incidence levels. VSD was a disease with the highest incidence and distribution in the cacao plantations. Besides, this study also described the symptom of the disease.